THE VIABILITY OF AN INTEGRATIVE FRAMEWORK FOR URBAN DESIGN AND REGIONAL ENVIRONMENTAL JUSTICE - T.F. Poon, Stephen (PLANNING MALAYSIA, 2018)
Environmental justice is an increasingly problematic proposition, as the clash of political, economic, social and community interests invariably occur. The purpose of this research is to examine the viability of an integrated framework that establishes environmental justice from economic, social and cultural development perspectives in Malaysia. Case studies analysing Iskandar Low Carbon Blueprint (LCB) 2025 and the River of Life Project (ROL) are presented. Findings suggest that clear national policies on urban transformation is an increasingly important environmental justice issue in Malaysia, but sustaining liveability is a challenge in the face of more critical decisions on infrastructural and resource management and energy use, resulting in a lack of attitudinal and behavioural change in urban planning programmes. This suggests that meaningful stakeholder engagements and collaborations contribute in planning economically and ecologically viable solutions and initiatives for liveable and resilient cities.